Back Cover. Issue 4 (6th July 2022) - Unknown
Abstract : Plasma surface modification is one of the promising nanomaterials strategies due to the high efficiency, rapid processing, versatility, and small environmental impact. This timely review summarizes the recent progress and prospects of plasma‐tailored defective electrocatalysts for water electrolysis and hydrogen fuel cells. Challenges, opportunities, and future roadmap are discussed, offering insights into the structural tailoring of nanocatalysts via plasma technologies. Abstract : Plasma surface modification is one of the promising nanomaterials strategies due to the high efficiency, rapid processing, versatility, and small environmental impact. This timely review summarizes the recent progress and prospects of plasma‐tailored defective electrocatalysts for water electrolysis and hydrogen fuel cells. Challenges, opportunities, and future roadmap are discussed, offering insights into the structural tailoring of nanocatalysts via plasma technologies.